(untitled) (Bangladesh Journal of Neuroscience, 2026)
Background: Management of stroke patients in low resource settings like Bangladesh largely depends upon their caregivers who are mostly unskilled family members. The effect of a structured caregiver-training program on stroke patients has not been studied adequately in Bangladesh. This study was conducted to evaluate the effect of caregivers’ training in improving outcome of stroke patients. Methods and Materials: This assessor blind randomized controlled trial was performed in the Department of Neurology, Chittagong Medical College Hospital, Chattogram for a period of two years. One hundred and fortynine stroke patients and their care givers were randomly divided into two groups: the intervention arm and the control arm. Caregivers in the intervention arm received actively two sessions of training according to modified London Stroke Carers Training Course manual before their patients are discharged from the hospital. The functional status of patients from both groups was evaluated by the Barthel Index score (BI) and Modified Rankin scale (MRS) score at base line and at two, four and six months. Results: Baseline characteristics and functional status of patients and caregivers of both arms were similar (p=>0.05). Median value of interval from stroke onset to hospitalization was 1 and 0 days in the intervention and control arm, respectively (p=0.897) and median length of stay in hospital was 5 days in both arms (p=0.360). Patients in the intervention arm had significant improvement in their median BI from baseline to 6 months (10 and 100; p=<0.001). Similarly, patients in the control arm also had significant improvement in their BI in the same period (15 and 70; p=<0.001). However, the intervention arm had better median BI at two, four and six months follow-up periods (p = <0.001, p = 0.001 and p = <0.001 respectively) than the control arm. Moreover, significantly more patients achieved BI e”60 (representing functional independence) after 6 months in the intervention arm than the control arm (90.4% versus 74.4% respectively; p=0.038). Better improvement was also observed in MRS score in intervention arm (p = 0.001, p = 0.002 and p = 0.037 at 2, 4 and 6 months respectively) than the control arm. Six-month mortality rate was higher in the control arm (27%) than intervention arm (18.7%) but difference was not statistically significant (p=0.224). Conclusions: Training of caregivers of post-stroke inpatients resulted improved functional independency of stroke patients and it might be helpful for the home management of such patients. It is important to explore different methods of caregiver training program to find out the best one suitable in our settings.